Comparative analysis of the res judicata doctrine under English Law - Zarzalejos Herrero, Jaime (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
The paper analyses the regulation of the res judicata doctrine under English and Spanish law from a comparative perspective. The paper first examines the regulation of the res judicata doctrine –and other pleas which have similar effects– under English law. Secondly, the paper reviews its regulation under Spanish law. The paper ends drawing some conclusions on the differences and similarities under both legal systems.